Strategi City Branding dalam meningkatkan Minat berkunjung Wisatawan pada Festival Budaya Tabut Bengkulu - Twenty Mariza Syafitri; Maya Novianti; Darwan Effendi (Journal of Trends Economics and Accounting Research, 2023)
The contribution of the tourism industry is one step of the government's strategy to improve the economic welfare of the community. Tourism management can encourage people to take advantage of opportunities created by various activities that can provide of profit. This condition will also contribute to business sustainability for the community in the surrounding environment. One strategy that can be implemented by the Regional Government of Bengkulu Province is through a city branding strategy to increase tourist interest in visiting the Bengkulu Tabut Cultural Festival. The Tabut Cultural Festival activities can be one of tourism promotion for Bengkulu Province to help the government introduce and invite the interest of local tourists, national tourists, or international tourists to travel in Bengkulu Province, and is expected to increase regional income. This research aims to determine: (1) the influence of city branding on destination image. (2) the influence of destination image on nostalgic emotions. (3) the influence of destination image on memorable tourism experiences. (4) the influence of nostalgic emotions on memorable tourism experiences. (5) the influence of nostalgic emotions on tourists' interest of visit the Tabut Bengkulu Cultural Festival, and (6) the influence of memorable tourism experience on tourists' interest of visit the Tabut Bengkulu Cultural Festival. This type of research is quantitative research using a causal study approach. The sample for this research was 327 visitors to the Bengkulu Tabut Festival using incidental sampling techniques. The data analysis method uses the SEM-SmartPLS program. The results of this research show that city branding has a significant effect on destination image, Destination Image has a significant effect on Nostalgic Emotion, nostalgic emotion has a direct effect on Memorable Tourism Experience, Destination Image has a significant effect on Memorable Tourism Experience, nostalgic emotion has a significant effect on on tourists' interest of visit the Tabut Bengkulu Cultural Festival, as well as the Memorable Tourism Experience has a significant influence on tourists' interest of visit the Tabut Bengkulu Cultural Festival